IMPLEMENTASI ALGORITMA DECISION TREE DALAM OPTIMASI PENILAIAN KINERJA OPERASIONAL - Maulana, Rijwan; Hassolthine, Cian Ramadhona; Saputra, Muhammad Ikhwani (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
Companies nowadays derive significant benefits from adopting digital systems in their operations. Politeknik LP3I Jakarta, for example, an educational institution, has implemented digitalization to optimize operational performance assessments by auditors. Manual audit assessments consume significant time and effort. Applying intelligent algorithms, such as Decision Tree, has become key to enhancing efficiency and accuracy in decision-making during assessments. The objective of this research is to evaluate the effectiveness of operational performance assessments by identifying and addressing these issues, implementing the Decision Tree algorithm. Decision Tree, which has evolved through a series of algorithms like C5.0, is the appropriate choice as it can make decisions based on specific conditions from the input data. The Decision Tree method and C5.0 Algorithm will help in rapidly and accurately calculating assessments based on criteria. This implementation can minimize manual audit activities, save time, and improve the accuracy of operational performance evaluations. The outcome of this research is higher efficiency in the operational performance assessment process, allowing auditors to focus on strategic aspects and in-depth analysis. Thus, Politeknik LP3I Jakarta and similar institutions can experience positive impacts from technology integration in their operational management, supporting progress and enhancing the quality of educational services.